Letter to Jane Tolmach from Glenn M. Anderson - Glenn M. Anderson:::::: (1966)
A letter from Glenn M. Anderson to Jane Tolmach after seeing her at a recent event at the Kennedys. He notes that the campaign is entering a difficult final stretch and emphasizes that support and friendship like hers are crucial to securing victory in November. Anderson closes by expressing hope to see her again soon.